A rapid and sensitive method for separation of Cu2+ ions from industrial wastewater sample and water samples with methacrylamide‐ethylene glycol dimethacrylate: A new synthesis of molecularly imprinted polymer - Fariborz Azizinezhad; Ali Moghimi (IET Nanobiotechnology)
Abstract In this study, new molecularly imprinted polymer particles (MIP) were synthesised to extract Cu2+ ions from aqueous solutions using radical polymerisation. MIP was developed using the methacrylamide‐ethylene glycol dimethacrylate (EGDMA) cross linking agent, methacrylamide monomer, and ACV initiator by the radical polymerisation method. A comparison of various cross linking agents in MIP production showed that the best cross linking agents are EGDMA and gallic acid. The template ions were removed by leaching with 0.100 M HCl. The polymer particles were characterised by FTIR spectroscopy, thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). The effect of different parameters such as cross linkers, pH, time, maximum adsorption capacity, and kinetic and isotherm adsorption were investigated. The best conditions were determined (pH = 8.0, t = 10 min, and qm = 262.53 mg g−1). The adsorption data were best fitted by Freundlich isotherm and pseudo second order kinetic models, as well. Due to its high adsorption capacity and multi‐layer behaviour, this method is an easy, fast and safe way to extract cations. Removal of Cu2+ in certified tap water and rain water was demonstrated and the industrial wastewater sample (Charmshahr, Iran) with which the MIP was developed using Methacrylamide‐ Ethylene Glycol Dimethacrylate (EGDMA) was good enough for Cu2+ determination in matrices containing components with similar chemical property such as Co2+, Zn2+, Fe2.